Organizational behavior - Schermerhorn, John R.; Hunt, James G.; Osborn, Richard N. (New York ; Chichester : John Wiley and Sons, 2000)
This book is divided into five parts: Environment; Managing individuals; managing groups; Managing organizations; and Managing processes.
Keywords: Management; Organization; Organizational behavior; Management